Hypericin in the Light and in the Dark: Two Sides of the Same Coin - Jendželovská, Zuzana; Jendželovský, Rastislav; Kuchárová, Barbora; Fedoročko, Peter (Frontiers in Plant Science, 2016)
Hypericin (4,5,7,4',5',7'-hexahydroxy-2,2'-dimethylnaphtodiantrone) is a naturally occurring chromophore found in plants of the genus Hypericum, especially Hypericum perforatum L. (St. John’s wort), and in some basidiomycetes (Dermocybe spp.) or endophytic fungi (Thielavia subthermophila). In recent decades, hypericin has been intensively studied for its broad pharmacological spectrum. Among its antidepressant and light-dependent antiviral actions, hypericin is a powerful natural photosensitizer that is applicable in the photodynamic therapy (PDT) of various oncological diseases. As the accumulation of hypericin is significantly higher in neoplastic tissue than in normal tissue, it can be used in photodynamic diagnosis (PDD) as an effective fluorescence marker for tumor detection and visualization. In addition, light-activated hypericin acts as a strong pro-oxidant agent with antineoplastic and antiangiogenic properties, since it effectively induces the apoptosis, necrosis or autophagy of cancer cells. Moreover, a strong affinity of hypericin for necrotic tissue was discovered. Thus, hypericin and its radiolabeled derivatives have been recently investigated as potential biomarkers for the non-invasive targeting of tissue necrosis in numerous disorders, including solid tumors. On the other hand, several light-independent actions of hypericin have also been described, even though its effects in the dark have not been studied as intensively as those of photoactivated hypericin. Various experimental studies have revealed no cytotoxicity of hypericin in the dark; however, it can serve as a potential antimetastatic and antiangiogenic agent. On the contrary, hypericin can induce the expression of some ABC transporters, which are often associated with the multidrug resistance (MDR) of cancer cells. Moreover, the hypericin-mediated attenuation of the cytotoxicity of some chemotherapeutics was revealed. Therefore, hypericin might represent another St. John’s wort metabolite that is potentially responsible for negative herb–drug interactions. The main aim of this review is to summarize the benefits of photoactivated and non-activated hypericin, mainly in preclinical and clinical applications, and to uncover the “dark side” of this secondary metabolite, focusing on MDR mechanisms.